Institutional Repository Sebagai Sarana Komunikasi Ilmiah Yang Sustainable Dan Reliable - Faizuddin Harliansyah (Pustakaloka, 2016)
Abstract; Institutional repositories development has drawn the attention of many scholars throughout the world. Using the keywords ‘institutional repositories’, there are over 300 peer-reviewed articles related on the topic has been indexed in Library, Information Science, & Technology Abstracts (LISTA) and SCOPUS. There are also hundreds of theses, dissertations, and websites dedicated on this blooming trends. These are proofs that the importance of IR in higher education has been acknowledged by many professionals in the field. This paper aims at clarifying the role of repositories in strengthening scholarly communication in higher education and research institution and explaining some basic repositories concepts (types of repositories and their characteristics), as well as exploring its relations with open access movement, the development ideas, and resources that could be kept in repositories and deposit policies.Abstrak; Pengembangan institutional repositories telah banyak menyita perhatian dari kalangan ilmiah di seluruh dunia. Melalui kata kunci ‘institutional repositories’, ada lebih dari 300 artikel terulas mitra bestari yang berhubungan dengan topik ini, yang telah terindeks di Library, Information Science, & Technology Abstracts (LISTA), dan SCOPUS. Terdapat juga ratusan tesis, disertasi, dan website yang mengulas trend ini. Inilah bukti bahwa pentingnya institutional repositories (IR) telah dipahami oleh para profesional di bidangnya. Tulisan ini akan menjelaskan aturan-aturan repository dalam memperkuat komunikasi ilmiah di perguruan tinggi dan lembaga riset, menjelaskan konsep-konsep dasar repositories, termasuk tipe-tipe repository dan karakteristiknya. Tulisan ini juga akan memperdalam konsep repositories dalam hubungannya dengan gerakan open access, pengembangan ide-ide, sumber-sumber ilmiah yang dapat disimpan di repositories, serta kebijakan penyimpanan di dalamnya.